Polyamide Nanofilms through a Non‐Isothermal‐Controlled Interfacial Polymerization - Zhao, Guang‐Jin; Li, Lu‐Lu; Gao, Hai‐Qi; Zhao, Zhi‐Jian; Pang, Zi‐Fan; Pei, Chun‐Lei; Qu, Zhou; Dong, Liang‐Liang; Rao, De‐Wei; Caro, Jürgen; Meng, Hong (Advanced functional materials, 2024)
Efficient thin film composite polyamide (PA) membranes require optimization of interfacial polymerization (IP) process. However, it is challengeable owing to its ultrafast reaction rate coupled with mass and heat transfer, yielding heterogeneous PA membranes with low performance. Herein, a non‐isothermal‐controlled IP (NIIP) method is proposed to fabricate a highly permeable and selective PA membrane by engineering IP at the cryogenic aqueous phase (CAP) to achieve synchronous control of heat and mass transfer in the interfacial region. The CAP also enables the phase transition of the aqueous solution from the liquid to solid state, providing a more comprehensive understanding of the fundamental mechanisms involved in different phase states in the IP process. Consequently, the PA membrane exhibits excellent separation performance with ultrahigh water permeance (42.9 L m−2 h−1 bar−1) and antibiotic desalination efficiency (antibiotic/NaCl selectivity of 159.3). This study provides new insights for the in‐depth understanding of the precise mechanism linking IP to the performance of the targeting membrane. A non‐isothermal‐controlled IP method is proposed to fabricate a highly permeable and selective PA membrane by engineering IP at the cryogenic aqueous phase to achieve synchronous control of heat and mass transfer in the interfacial region. The membrane exhibits ultrahigh water permeance and antibiotic desalination efficiency.